A generation on the move: voices of youths in the context of climate change, migration, and livelihood transition - Nansambu, Daphne; Sugden, Fraser (CGIAR Research Program on Water, Land and Ecosystems, 2017)
What happens at a conference for youth about youth ? On the 28th and 29th of June 2017, Uganda hosted a youth summit as a side event to the 11th International Community Based Adaptation to Climate Change conference in Kampala, Uganda. It was focused on the theme “ Enhancing the ability of youth to build ecosystem resilience , ” . The CGIAR Research Program on Water Land and Ecosystems and the International Water Management Institute hosted a session titled “A youth agenda for sustainable agricultural transformation in an era of climate change and out - migration.” It was oriented around one key issue: a large population of rural youth today in Uganda and the wider region have limited interest in becoming farmers. Climate stress is becoming an increasingly important mediating factor in shaping the movement of youth out of the sector.